Investigation of liquid injection on rotary compressor performance - Lai, Zhau Yan (Nanyang Technological University, 2020)
Compressors have been around for a long time, but only recently has there been an increase application of swing vane compressors. They are here to replace the rolling piston compressors with its improved efficiency by reducing energy losses due to mechanical and noises. Some researchers have tried to further increase the swing vane compressors’ efficiency by recycling liquid refrigerant to cool the compressor. This is known as liquid injection. In this project, the aim is to investigate the effects of liquid injection on swing vane compressors by studying the cooling effects and the characteristics of the liquid injection. In order to do so, a chamber was designed and fabricated to mimic a swing vane compressor. An experimental set up was also built to carry out parametric studies to learn about the effects of liquid injection duration and chamber pressure on the cooling capacity. The results showed obvious cooling effects. As much as a 0.8°C drop is also observed while varying chamber pressure. For chamber temperature of 38°C, temperature drop of 0.3°C, 0.8°C, 1.9°C was seen for injection duration of 3.2ms, 4.6ms and 9.6ms, respectively. Although these temperature drops are at small quantity and they vary from calculated values, evidence point to the fact that Polyolester oil existed in the coolant was not considered during the experiment set up. The spray characteristic is also studied through the means of high-speed videography. Images from high-speed video of the liquid injection show how the liquid behaves under different chamber conditions.